Safety Promotion Through Educational Games Media Towards the Knowledge of Primary School Students - Sri Hapsari, Roro Retno; Widowati, Evi (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Primary school students are a group that potentially have accidents, this is due to the character of students who have high curiosity and exploration. A student's understanding of his own safety is inseparable from the cognitive limitations it has. Therefore, it is necessary to promote occupational safety and health to primary school students. This research was conducted to determine the impact of occupational safety and health promotion on the level of knowledge of primary school students.Methods: This research is a quasi-experimental with non-equivalent control group design. The research sample consists of 222 respondents, but only 126 respondents met the inclusion and exclusion criteria. Data analysis used the Wilcoxon test.Result: The results shows there is impact of occupational safety and health promotion on the knowledge of primary school students. This can be seen based on the significant difference in the knowledge level of primary school students who received occupational safety and health promotion (p value=0,000<0,05) and there was no significant difference in knowledge in the group that did not receive occupational safety and health promotion (p value=0,849>0,05).Conclusions: The conclusion finds that occupational safety and health promotion has impact on the knowledge level of primary school students.